Knowledge and Behavior of Antibiotic Use among PKK Women (Family Welfare Empowerment) with Career Women Status in Banjar Yangbatu Kauh, East Denpasar - Fitria Megawati; Ni Putu Dewi Agustini (Jurnal Ilmiah Medicamento)
Antibiotics are drugs that are often prescribed by doctors to treat infections. Lack of public knowledge about the use of antibiotics causes antibiotic resistance. To overcome the irrational use of antibiotics, it is necessary to increase the knowledge and behavior of parents about the use of antibiotics. The purpose of this study was to determine the level of knowledge and behavior of using antibiotics in PKK (Family Welfare Empowerment) mothers who were career women in the Yangbatu Kauh Banjar, East Denpasar. This research is a descriptive research using accidental sampling technique. The distributed questionnaires were tested for validity and reliability by distributing questionnaires to 30 trial respondents. The questionnaire is declared valid if it has a calculated r value > 0.361, and the Cronbach Alpha reliability test using SPSS version 22 was tested with a 95% confidence level, the questionnaire data was declared reliable with a value of 0.914 on the level of knowledge and a value of 0.810 on behavior. The results obtained based on the age characteristics of the most respondents, namely respondents aged 42-47 years as much as 51.28%. On the characteristics of the respondents based on the level of education the most were SMA/SMK as much as 58.97% and on the characteristics of the type of work the most were private employees as much as 64.10%. The level of knowledge of PKK mothers who are career women is in the good category with a percentage of 69.23% as many as 27 people and the behavior of PKK mothers who are career women is in the good category with a percentage of 82.05% as many as 32 people. So, from these results, PKK mothers who are career women in Banjar Yangbatu Kauh, East Denpasar have a good level of knowledge and behavior in the use of antibiotics.